PENGEMBANGAN PERANGKAT PEMBELAJARAN KONSEP JAMUR DI SEKOLAH MENENGAH ATAS - Samidi Samidi (Master Program of Biology Education, Universitas Lambung Mangkurat, 2019)
Based on clinical supervision at Loban 1 Public High School, most of the teachers have not developed their own learning tools, so that relevance to learning in schools needs to be addressed. This research & development uses the ASSURE development model on the Mushroom concept using the guided inquiry learning model and the 5M approach. The purpose of this study is to develop a mushroom concept learning device using a model of guided inquiry in high school that is valid, practical and effective. The subject of research & development is a learning device while the object of research is students of SMA 1 Loban River, Tanah Bumbu Regency. Individual trials were carried out in the X-MIA3 class, and small group tests in the X-MIA2 class and field tests were carried out in the X-MIA1 class. Data on the validity of learning devices include validation by three experts, data on the practicality of learning devices including assessment of the implementation of lesson plans, student responses to learning, observation of teacher and student activities during learning activities and the level of effectiveness of learning devices including a) cognitive and product learning outcomes. b) results of the assessment of performance skills, c) results of the assessment of social attitudes, d) results of spiritual attitude assessment, and e) results of the assessment of critical thinking skills. The results of the study showed that the learning devices that had been developed had fulfilled the indicators of validity, practicality, and effectiveness, thus the Mushroom concept learning tools developed by using the guided inquiry model and the 5M approach could already be used in learning activities.